miR-378a-5p targeting BRAF regulates CD4+T cells differentiation to Th1 under rEg.P29 induction - Zhang, Tingting; Mu, Hu; Wang, Chuan; Qian, Bingshuo; Zhu, Mingxing (Frontiers in Immunology, 2025)
IntroductionCystic echinococcosis (CE) is a globally distributed zoonotic disease caused by Echinococcus granulosus (Eg) that often presents with insidious onset and asymptomatic progression. Although several Eg-based recombinant vaccines have been developed for the prevention of CE, our previous study demonstrated that recombinant Eg.P29 (rEg.P29) is a potent immunogen that induces a robust Th1 immune response. Furthermore, microarray data from miRNA profiling of CD4+T cells isolated from mouse spleens showed that miR-378a-5p was significantly upregulated one week after immunization with rEg.P29.MethodsIn this context, bioinformatics predictions and dual-luciferase reporter assays identified BRAF as a direct miR-378a-5p target, with downstream signaling involving the MAPK/ERK pathway.ResultsOur research demonstrated that rEg.P29 immunization increased miR-378a-5p expression in naïve CD4+T cells, reduced BRAF, MEK1/2, and ERK1/2 expression, and promoted Th1 differentiation while inhibiting Th2 differentiation. Overexpression of miR-378a-5p in naïve CD4+T cells yielded similar results, whereas knockdown of miR-378a-5p had the opposite effect.ConclusionIn summary, our findings reveal that under the induction of rEg.P29, miR-378a-5p targeted to BRAF regulation and initiated the differentiation of CD4+T cells in mouse spleen to Th1 direction, and MAPK/ERK pathway may be involved in this process, identifying miR-378a-5p as apotential biomarker and immunomodulatory target in CE.